Analysis and implications of the determinants of CIRR for the seamless execution of PPP projects - Kang-Soo Kim (Korea Development Institute (KDI), 2020)
The contracted internal rate of return (CIRR) of Korea's public-private-partnership (PPP) projects does not properly reflect the risks associated with the different types and characteristics of facilities and government support. Rather, the rates are set at the same level as similar preceding projects. - The characteristics of a project, e.g. facility type, amount of private investment, and operation period, and the ensuing risks are not sufficiently reflected in the decisions over CIRR. Moreover, the construction subsidy―a government risk-sharing and support policy-inadequately contributes to lowering the rate. - The project review period and VfM test do not have a meaningful effect on determining the CIRR, implying that project evaluations and analyses need to be improved. ■ For the seamless execution and invigoration of PPP projects and lower user fees, the CIRR must be fixed at an appropriate level through more active negotiations and efforts in addition to taking the CIRR of similar existing PPP projects into account. - A significantly low CIRR relative to the risks could diminish the incentive to privately invest or could even lead to the bankruptcy of an ongoing project. On the other hand, an excessively high rate could raise the user fee or necessitate larger government subsidies. - To determine the suitable CIRR, the risks and effects of government support must be analyzed. In particular, policies that encourage competition in the PPP market must be developed to lower user fees through policies, e.g. transparent disclosure of information, simplified implementation procedures, increased provision of guarantees, and the provision of compensation for the cost of failed proposals, etc.
Keywords: 330